Florid Cemento-Osseous dysplasia - A hidden inquest - Dathar, Sahithi; Reddy, Sudhakara; Sai Kiran, CH; Ramesh, Tatapudi; Rajesh, N; Divya Teja, DV (International Journal of Medicine, 2015)
Florid cemento-osseous dysplasia (FCOD) is a rare distinguishable condition that characteristically affects the jaws of middle aged women. It is usually symmetrical on both sides and manifests radiographically as diffuse, lobulated multiple sclerotic radio-opacities involving all the quadrants of the jaws. The lesion is mostly benign and requires no treatment unless the patient is symptomatic. For the asymptomatic patient the best management advisable is regular recall checkups and reinforcement of good oral hygiene. Herewith, we are reporting one such rare entity of a 37 year old female patient.
Keywords: Florid Cemento-Osseous Dysplasia; Fibro-Osseous Lesion.